2021
DOI: 10.1063/5.0054802
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of subwavelength topological interface states in locally resonant metastructures with shunted piezoelectric patches

Abstract: We investigate the propagation behavior of the low-frequency topological interface state of the flexural wave in the locally resonant metastructure and analyze the tunability of the sub-wavelength interface states by the piezoelectric shunting circuit. One homogeneous thin beam is periodically attached with local resonant beams, which connect shunted piezoelectric actuators. The folding band obtained by merging two primitive unit cells into one new element can generate a Dirac point below the low-frequency loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Some researchers have employed the piezoelectric shunt method [39][40][41][42] to manipulate the frequency range of the valley TPES and further realize reconfigurable TIs. Zhou et al [43] developed a tunable QVHE membrane-type metamaterial.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have employed the piezoelectric shunt method [39][40][41][42] to manipulate the frequency range of the valley TPES and further realize reconfigurable TIs. Zhou et al [43] developed a tunable QVHE membrane-type metamaterial.…”
Section: Introductionmentioning
confidence: 99%
“…The x, y and z directions are denoted as 1, 2 and 3 respectively. Since the piezoelectric sheet is subjected to an electric field along the z-axis only, the intrinsic equation of the piezoelectric material in the plane stress state can be expressed as [47,53,54]…”
Section: Structural Design and Topological Energy Band Inversion Of T...mentioning
confidence: 99%
“…By using the piezoelectric control technique, Li et al controlled the appearance and disappearance of the double Dirac cone by adjusting negative capacitance circuits connected to piezoelectric sheets, and verified the strong robustness of the topological waveguide in the experiments [47]. Piezoelectric shunt technology was first proposed by Forward, as well as being well developed for active control in the field of sound and vibration [48][49][50][51][52][53][54]. By connecting a negative capacitance circuit to the piezoelectric sheet of the metamaterial plate, it can be regarded as an element of adjustable stiffness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy localization is observed for excitations at the interface mode's frequency. Including local resonators enables topological bandgaps in low frequencies and subwavelength topological interface states [6][7][8][9]. In this framework, present-day progress has shown that topological transitions in 1D systems can be obtained by only adjusting the local resonator properties without additional modifications in the host structure [10].…”
Section: Introductionmentioning
confidence: 99%